2010
DOI: 10.1002/pssc.200983179
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic incorporation in MBE‐grown HgCdTe studied with the use of ion milling

Abstract: Ion milling was employed for the study of arsenic incorporation in molecular beam epitaxy‐grown Hg0.8Cd0.2Te films doped in situ. The behaviour of specific defects, which formed after injection of mercury interstitials provided by the milling, allowed for estimating density of electrically active arsenic atoms. It is confirmed that the most efficient incorporation of As occurs when arsenic flux cracking is used, at the cracking zone temperature Tcr > 700 °C. Growth with doping without cracking was found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
5
1
Order By: Relevance
“…Interestingly, however, in samples 1 and 3 the electron mobility extracted with DMSA right after the milling appeared to be higher than that in the as−grown samples. This contrasts these films to other MCT samples studied earlier [10,11,16,19,20], and could be explained by partial de−compensation of the film occurring via Hg vacancy filling and formation of donor complexes comprising As atoms, as described below, along with the relatively low total concentration of donor complexes right after ion milling.…”
Section: Electrical Properties Of Ion-milled Filmscontrasting
confidence: 73%
See 3 more Smart Citations
“…Interestingly, however, in samples 1 and 3 the electron mobility extracted with DMSA right after the milling appeared to be higher than that in the as−grown samples. This contrasts these films to other MCT samples studied earlier [10,11,16,19,20], and could be explained by partial de−compensation of the film occurring via Hg vacancy filling and formation of donor complexes comprising As atoms, as described below, along with the relatively low total concentration of donor complexes right after ion milling.…”
Section: Electrical Properties Of Ion-milled Filmscontrasting
confidence: 73%
“…The measurements performed on the samples which were subjected to a number of steps of chemical etch− ing, showed that these values of donor concentration per− sisted throughout the whole film. Such values of residual donor concentration are typical of MCT films grown on GaAs substrates by MBE [10,11], and of MOCVD films grown with the other technology [20].…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…It appears, that strongly non-equilibrium processes which take place under IM, when material is oversaturated with interstitial mercury atoms Hg I generated near the surface [1][2], lead to the appearance of specific defect complexes, which may not form under other conditions. These complexes may also comprise intrinsic point and extended defects that normally do not show their presence due to their electrical neutrality or compensation [4,10].…”
Section: Introductionmentioning
confidence: 99%